If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (i)(1 + 8i) = 0 (1 * i + 8i * i) = 0 (1i + 8i2) = 0 Solving 1i + 8i2 = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), 'i'. i(1 + 8i) = 0Subproblem 1
Set the factor 'i' equal to zero and attempt to solve: Simplifying i = 0 Solving i = 0 Move all terms containing i to the left, all other terms to the right. Simplifying i = 0Subproblem 2
Set the factor '(1 + 8i)' equal to zero and attempt to solve: Simplifying 1 + 8i = 0 Solving 1 + 8i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 8i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 8i = 0 + -1 8i = 0 + -1 Combine like terms: 0 + -1 = -1 8i = -1 Divide each side by '8'. i = -0.125 Simplifying i = -0.125Solution
i = {0, -0.125}
| 3x+21=10x | | 3(x-2)=30 | | 15+6k=7+7k | | 5(10x-10)=-5(4x+4) | | -40-8k=-8(1+5k) | | 70-q-q-2q=90 | | -3(.25)+.6=7+x+y | | 21-2(5r+3)=-6r+1-2r | | 25=3u-4 | | 1y=5+2x | | 12=-4+4x | | x(6)+x(7)=52 | | 4.4+6.2=8.8s-1.8 | | -5v+2v=-8+14 | | C=0.41+0.26(z-1) | | 5(4x-2)=33 | | 3.93-15.3g=4.53-15g | | -(n-6)-8=-(1+n) | | -5u^2+24u=-5 | | 60x+30(60)=50x+50(60) | | 19+20h=-134(-5h-8) | | -2-11x=-35 | | 5x-14-7x+4=2-8x-8+2x | | .6y-3x=x+y+7 | | -(n-6)-8=(1+n) | | -3(-f-1)=3f+3 | | -2(y+7)=16 | | 8=-4(3-10p)+7p | | 27-6=17x-26 | | X-8=-36+5x | | -14x-7=133 | | 70x+15(80)=60x+60(80) |